RESEPSI KHALAYAK TERHADAP SELF-ACCEPTANCE DALAM MEDIA FILM (The Commercium, 2021)
Film media is one form of mass media that plays an important role in the socio-cultural, artistic, political and scientific world. The presence of film media has an impact as a medium of mass communication which is considered effective, not only entertainment, but its presence can be a medium of information in many aspects, such as education, which can include psychological conditions and social impacts. Which then made Ernest Prakasa make a film that raised concerns about the Body-shamming issue which is increasingly prevalent among the public, entitled Imperfect with the aim of being able to give a positive message, namely the concept of Self-Acceptance to the audience. This study aims to examine the acceptance of active audiences in responding to the concept of Self-Acceptance in respondents after watching the film Imperfect. The research method used is reception analysis method involving 7 informants who have been interviewed in depth with age backgrounds, different physical characteristics and informants who are experiencing a self-crisis. The results of this study indicate that the meaning of Self-Acceptance carried out by the informants is the result of from the point of view that is in his mind according to the experience that the informant has experienced, so that these different experiences will lead to various different interpretations from the informant's point of view regarding the concept of Self-Acceptance in the film Imperfect.